Comparison of FACTS Devices for Two Area Power System Stability Enhancement using MATLAB Modelling - J. N. Rai; Naimul Hasan; B. B. Arora (International Journal of Applied Power Engineering (IJAPE), 2014)
Modern Power Transmission networks are becoming increasingly stressed due to growing demand and restrictions on building new lines. Losing stability is one of the major threat of such a stressed system following a disturbance. Flexible ac transmission system (FACTS) devices are found to be very effective in a transmission network for better utilization of its existing facilities without sacrificing the desired stability margin. The static synchronous compensator (STATCOM) and Static Var Compensator (SVC) are the shunt devices of the flexible AC transmission systems (FACTS) family. When system voltage is low, STATCOM generates reactive power and when system voltage is high it absorbs reactive power whereas the Static Var compensator provides the fast acting dynamic compensation in case of severe faults. In this Paper, the performance of SVC is compared with the performance of STATCOM. Proposed controllers are implemented using MATLAB/SIMULINK. Simulation results indicate that the STATCOM controller installed with two machine systems provides better damping characteristics in rotor angle as compared to two machine system installed with SVC. Thus, transient stability enhancement of the two machine system installed with STATCOM is better than that installed with SVC.